Analysis of Usage Barriers of Interactive Mobile Devices among the Elderly Based on the Technology Acceptance Model - Yue, Xiaoguang; Huang, Zhan; Zhan, Yin; Wang, Fen; Efendiev, Rakib (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This paper aims to analyze the problems and barriers faced by the elderly when using interactive mobile devices in order to propose practical solutions. Based on the technology acceptance model (TAM), this study takes perceived usefulness (PU), perceived ease of use (PEOU), and usage intention as core latent variables; and extends the latent variables to include new technology anxiety (NTA), operational complexity (OCP), physiological function limitations (PFL), aging-friendly design (AFD), quality of intergenerational support (ISQ), and demand matching. The research objects are elderly people over 60 years old. Data are collected through questionnaires, and structural equation modeling (SEM) is used to quantitatively analyze the impact intensity of various barrier factors. The final results show that PU and PEOU jointly affect usage intention, determining the elderly’s acceptance of interactive mobile devices; meanwhile, PEOU determines PU. The conclusions of this paper provide empirical evidence for the aging-friendly transformation and intervention measures of interactive mobile devices.